Out of the attic [large type] - Andrews, V. C. (Virginia C.) (Andrews, V. C. (Virginia C.). Dollanganger family series, 2020)
Married to the handsome, wealthy Garland Foxworth following a wildfire romance, and an unexpected pregnancy, young Corrine Dixon finds her life very different from how she imagined it. Often alone in the mansion of Foxworth Hall, she can practically feel the ancestors' judgment of her as insufficient--as not a Foxworth. Stern portraits glare at her from the walls, and the servants treat her strangely. Nothing in the vast place is truly hers. Even her son, Malcolm Foxworth, born in the luxe Swan Room and instantly whisked away to a wet nurse, feels alien to her. With a husband alternately absent and possessively close, Corrine doesn't yet realize that she's barely scratched the surface of what lies beneath Foxworth Hall's dark facade and the family that guards its legacies. With the fortieth anniversary celebration of Flowers in the Attic, and ten new Lifetime movies in the past five years, there has never been a better time to experience the forbidden world of V.C. Andrews"--Provided by publisher.